The Administrative Judiciary Reforms in the Czech Republic - Kandalec, Pavel (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The present shape of the administrative judiciary in the Czech Republic is the result of events before January 1, 2003, when the present Supreme Administrative Court was established. This date is crucial, and everything that happened before it should be seen as elements of historical development of the administrative judiciary. Therefore, the study distinguishes two periods in the history of the development of the Czech administrative judiciary: 1) the activity of the Czechoslovak Supreme Administrative Court in 1918−1952 and 2) the activity of the administrative judiciary in 1992−2002. The next part of the study presents the current state of the Czech administrative judiciary, highlighting the importance of the judicial activity of the Supreme Administrative Court and the actions of the legislator aimed at eliminating the problem of overloading this court. The result of these actions by the legislator was the reform carried out in 2021, consisting in limiting access to the court of second instance in certain cases.